2015
DOI: 10.5194/pb-2-111-2015
|View full text |Cite
|
Sign up to set email alerts
|

Tree shrews at the German Primate Center

Abstract: Abstract. For many years, Tupaia (family Tupaiidae), most commonly known as tree shrews, have been studied almost exclusively by zoologists resulting in a controversial debate on their taxonomic status among mammals. Today, tree shrews are placed in the order Scandentia; they are valuable, widely accepted and increasingly used model animals as an alternative to rodents and non-human primates in biomedical research. After a brief description on how tree shrews entered science and their taxonomic odyssey, the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 68 publications
0
1
0
Order By: Relevance
“…presented a genome sequence for the Chinese tree shrew (Fan et al., 2013) and showed that the tree shrew has close affinity to primates by characterizing key factors and signaling pathways in the nervous system and immune system. Compared to other large non-human primates such as monkeys or orangutans, the tree shrew has several characteristics or advantages more suitable for use as experimental animals, such as its small body, easy ability to feed, and short reproductive cycle and lifespan (Fuchs, 2015; Xu et al., 2012). The tree shrew has been proposed to be a viable and alternative animal model to primates in disease studies and drug safety testing.…”
Section: Introductionmentioning
confidence: 99%
“…presented a genome sequence for the Chinese tree shrew (Fan et al., 2013) and showed that the tree shrew has close affinity to primates by characterizing key factors and signaling pathways in the nervous system and immune system. Compared to other large non-human primates such as monkeys or orangutans, the tree shrew has several characteristics or advantages more suitable for use as experimental animals, such as its small body, easy ability to feed, and short reproductive cycle and lifespan (Fuchs, 2015; Xu et al., 2012). The tree shrew has been proposed to be a viable and alternative animal model to primates in disease studies and drug safety testing.…”
Section: Introductionmentioning
confidence: 99%
“…Tree shrews (Tupaia belangeri) are small body-sized omnivorous mammals that belong to the Scandentia order (Fuchs, 2015). Tree shrews inhabit the tropical forests and plantation areas in Southeast Asia (Fuchs & Corbach-Söhle, 2010).…”
Section: Introductionmentioning
confidence: 99%